Molybdenum Disulfide/Nitrogen-Doped Reduced Graphene Oxide Nanocomposite with Enlarged Interlayer Spacing for Electrocatalytic Hydrogen Evolution - Tang, Yu-Jia; Wang, Yu; Wang, Xiao-Li; Li, Shun-Li; Huang, Wei; Dong, Long-Zhang; Liu, Chun-Hui; Li, Ya-Fei; Lan, Ya-Qian (Advanced energy materials, 2016)
Facile design of low‐cost and highly active catalysts from earth‐abundant elements is favorable for the industrial application of water splitting. Here, a simple strategy to synthesize an ultrathin molybdenum disulfide/nitrogen‐doped reduced graphene oxide (MoS2/N‐RGO‐180) nanocomposite with the enlarged interlayer spacing of 9.5 Å by a one‐step hydrothermal method is reported. The synergistic effects between the layered MoS2 nanosheets and N‐doped RGO films contribute to the high activity for hydrogen evolution reaction (HER). MoS2/N‐RGO‐180 exhibits the excellent catalytic activity with a low onset potential of −5 mV versus reversible hydrogen elelctrode (RHE), a small Tafel slope of 41.3 mV dec−1, a high exchange current density of 7.4 × 10−4 A cm−2, and good stability over 5 000 cycles under acidic conditions. The HER performance of MoS2/N‐RGO‐180 nanocomposite is superior to the most reported MoS2‐based catalysts, especially its onset potential and exchange current density. In this work, a novel and simple method to the preparation of low‐cost MoS2‐based electrocatalysts with the extraordinary HER performance is presented. A simple strategy to synthesize an ultrathin molybdenum disulfide/nitrogen‐doped reduced graphene oxide (MoS2/N‐RGO‐180) nanocomposite with the enlarged interlayer spacing of 9.5 Å is reported. MoS2/N‐RGO‐180 exhibits excellent hydrogen evolution reaction (HER) catalytic activity with a low onset potential of −5 mV versus RHE, a small Tafel slope of 41.3 mV dec−1 and good stability over 5000 cycles.